Design of PID temperature control system based on STM32 - Zhang, Jianxin; Li, Hailin; Ma, Kai; Xue, Liang; Han, Bianhua; Dong, Yuemeng; Tan, Yue; Gu, Chengru (IOP conference series. Materials Science and Engineering, 2018)
A rapid and high-accuracy temperature control system was designed using proportional-integral-derivative (PID) control algorithm with STM32 as micro-controller unit (MCU). The temperature control system can be applied in the fields which have high requirements on the response speed and accuracy of temperature control. The temperature acquisition circuit in system adopted Pt1000 resistance thermometer as temperature sensor. Through this acquisition circuit, the monitoring actual temperature signal could be converted into voltage signal and transmitted into MCU. A TLP521-1 photoelectric coupler was matched with BD237 power transistor to drive the thermoelectric cooler (TEC) in FTA951 module. The effective electric power of TEC was controlled by the pulse width modulation (PWM) signals which generated by MCU. The PWM signal parameters could be adjusted timely by PID algorithm according to the difference between monitoring actual temperature and set temperature. The upper computer was used to input the set temperature and monitor the system running state via serial port. The application experiment results show that the temperature control system is featured by simple structure, rapid response speed, good stability and high temperature control accuracy with the error less than ±0.5°C.